Responses of cuticular waxes of faba bean to light wavelengths and selection of candidate genes for cuticular wax biosynthesis. Issue 3 (30th October 2020) - Huang, Lei; Xiao, Qianlin; Zhao, Xiao; Wang, Dengke; Wei, Liangliang; Li, Xiaoting; Liu, Yating; He, Zhibin; Kang, Lin; Guo, Yanjun
Abstract: Cuticular waxes play important eco‐physiological roles in protecting plants against abiotic and biotic stresses and show high sensitivity to environmental changes. In order to clarify the responses of cuticular waxes on faba bean ( Vicia faba L.) leaves to different light wavelengths, the phenotypic plasticity of cuticular waxes was analyzed when plants were subjected to white, red, yellow, blue, and purple light. Leaf samples from yellow, purple, and white lights were further analyzed, and candidate genes of wax biosynthesis were selected by RNA‐seq technology and transcriptome processing. Yellow light increased the total wax coverage and changed the crystal structure compared with leaves under white light. Light wavelengths changed the relative abundance of dominant primary alcohol from C24 under white, yellow, and red lights to C26 under blue and purple lights. In total, 100, 194 unigenes were obtained, and 10 genes were annotated in wax biosynthesis pathway, including VLCFAs elongation (KCS1, KCS4, LACS2 and LACS9), acyl reduction pathway (FAR3 and WSD1), and decarboxylation pathway (CER1, CER3 and MAH1). qRT‐PCR analysis revealed that yellow and purple lights significantly influenced the expression levels of these genes. Yellow light also increased the water loss rate and decreased the photosynthesis rate. Light at different wavelengths particularly yellow light induced the changes of phenotypic plasticity of cuticular waxes, which thus altered the leaf eco‐physiological functions. The expression levels of genes related to wax biosynthesis were also altered by different light wavelengths, suggesting that light at different wavelengths may also be applied in selecting candidate genes involved in wax biosynthesis in other crops.